Effects of low-frequency and high-frequency electroacupuncture pretreatment on the COX-2/mPGES-1/PGE2 pathway in a rat model of cold-coagulation dysmenorrhea - Song, Yue; Ni, Jinxia; Yuan, Jingxue; Zhang, Ziniu; Wang, Dinghao; Xiong, Zhihao (Frontiers in Immunology, 2025)
Primary dysmenorrhea (PD) refers to a condition in which women experience cyclic lower abdominal pain, often accompanied by lower back pain, and even severe pain and fainting around menstruation, significantly affecting daily activities and work. Inflammatory factors such as prostaglandins PGF2α, PGE2, and COX-2 play key roles in the pathological mechanisms of PD. Nonsteroidal anti-inflammatory drugs (NSAIDs) and hormonal contraceptives are the first-line treatments for dysmenorrhea; however, they have significant side effects. Electroacupuncture, as a non-invasive and effective therapeutic method, is widely used as a complementary and alternative treatment, although its mechanism of action remains unclear.MethodsA cold-coagulation type dysmenorrhea model was established in rats, which were divided into the control group, model group, low-frequency electroacupuncture group (2/10 Hz), and high-frequency electroacupuncture group (20/100 Hz). Behavioral writhing responses, organ indices, uterine tissue morphology changes, and levels of PGF2α, PGE2, COX-2, and other inflammatory markers were measured to evaluate the effects of the treatments.ResultsBoth the low-frequency electroacupuncture group and the high-frequency electroacupuncture group significantly reduced writhing scores, increased spleen index, decreased prostaglandin PGF2α and COX-2 levels, and increased prostaglandin PGE2 and β-EP levels to varying degrees.DiscussionBoth low-frequency and high-frequency electroacupuncture exert their anti-inflammatory and analgesic effects by activating the COX-2/mPGES-1/PGE2 pathway and mediating the increased release of the opioid peptide β-EP, which alleviates inflammatory pain. Both treatments achieve the therapeutic goal of treating PD, with high-frequency electroacupuncture demonstrating superior anti-inflammatory and analgesic effects compared to low-frequency electroacupuncture.